Cultural Content Analysis of English Textbooks Used by Tenth Graders in Bengkulu Utara - Zelvia Liska Afriani; Soni Mirizon; Margaretha Dinar Sitinjak (LINGUA: Jurnal Bahasa dan Sastra, 2019)
Abstract: This study aims at investigating cultural content in the textbooks in terms of four frameworks namely cultural types, cultural themes, cultural dimensions, and cultural senses. A content analysis under the paradigm of qualitative study was employed. Three English textbooks published by the government and Erlangga were chosen as the objects in this study. Additionally, teachers’ voice was needed in order to support and enrich the analysis. Results of the study showed that the textbook published by the government was heavily loaded with cultural aspects dealing with Indonesian culture, followed by target culture and international target culture whereas two textbooks published by Erlangga presented target culture as the highest percentage, which then followed by source culture and international target culture. In terms of cultural themes, those three textbooks contained bigger portion of big ‘C’ than little ‘c’. For cultural dimensions, the appearance of persons dominates all forms of the textbooks while semantic sense has the highest rank for cultural senses. In relation to teachers’ opinion of the textbooks, they felt unsatisfied on the distribution of the cultural content and hoped that the textbooks could provide more materials regarding Indonesian culture instead of target culture. These results lead to the conclusion that textbook writers should revise and reconsider the cultural content that should be introduced in the textbooks.Keywords: Cultural content, content analysis, English textbooksAbstrak: Penelitian ini bertujuan untuk menginvesitgasi muatan budaya yang ada dalam buku teks dari empat sisi yaitu dari jenis budaya, tema budaya, dimensi budaya, dan indra budaya. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan metode analisis isi. Terdapat tiga buku teks bahasa Inggris yang diterbitkan oleh pemerintah dan Erlangga yang dipilih menjadi objek dalam kajian ini. Selain itu, pendapat dari para guru juga diperlukan dalam rangka mendukung dan memperkaya analisis. Hasil penelitian menunjukkan bahwa hanya buku teks yang diterbitkan oleh pemerintah sangat sarat dengan aspek budaya yang berhubungan dengan budaya Indonesia, diikuti dengan budaya target dan budaya target internasional sedangkan dua buku yang diterbitkan oleh Erlangga menargetkan budaya target sebagai persentase tertinggi, yang kemudian diikuti oleh budaya sumber dan budaya target internasional. Dalam hal tema budaya, tiga buku teks tersebut berisi porsi budaya yang terlihat (‘C’) lebih banyak daripada budaya yang tidak terlihat (‘c’). Untuk dimensi budaya, aspek ‘orang’ mendominasi semua bentuk buku pelajaran. Dari sisi indra budaya, aspek semantik memiliki peringkat tertinggi. Hasil dari wawancara dengan para guru menunjukan ada rasa ketidakpuasan terhadap distribusi konten budaya yang ada, Pemerintah dan penerbit buku diharapkan dapat menyediakan buku pelajaran bahasa Inggris yang lebih banyak berisi materi tentang budaya Indonesia, bukan budaya target. Hasil ini mengarah pada kesimpulan bahwa penulis buku teks harus merevisi dan mempertimbangkan kembali konten budaya yang harus diperkenalkan dalam buku pelajaran bahasa Inggris.Kata-kata kunci: Analisis isi, konten budaya, buku teks bahasa Inggris